UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) AGRICULTURAL INTERVENTION THROUGH MICRO-FINANCE AND POVERTY ALLEVATION IN UYO METROPOLIS, AKWA IBOM STATE, NIGERIA. - Amokeye, Adalikwu, Rose; Offiong M., Isa; Beauty, Usoroh, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study assessed United Nations Development Programme (UNDP) micro-finance service and poverty alleviation in Uyo local government area of Akwa Ibom State, Nigeria. It determined micro credit programme, increase income of farmers and improvement in farmers’ status as they relate to poverty alleviation. Survey research design was adopted and was conducted in 4 clans of study area. Eight villages within these strata were purposively studied on the basis of micro credit beneficiaries. Altogether 240 rural farmers were involved. Data were obtained using questionnaire and analyzed using Pearson product moment correlation coefficient. Findings showed that average income of farmers increased after participation in UNDP micro-finance service. It was established that farmers experience improvement in their social status. Therefore, participating in the UNDP programme has a positive impact in farmers’ income level and